First Report on Rigid Plate Fixation for Enhanced Sternal Closure in Minimally Invasive Cardiac Surgery: Safety and Outcomes - Jules Miazza; Benedikt Reuthebuch; Florian Bruehlmeier; Ulisse Camponovo; Rory Maguire; Luca Koechlin; Ion Vasiloi; Brigitta Gahl; Luise Vöhringer; Oliver Reuthebuch; Friedrich Eckstein; David Santer (Bioengineering)
Introduction: This study reports of the use of a rigid-plate fixation (RPF) system designed for sternal closure after minimally invasive cardiac surgery (MICS). Methods: This retrospective analysis included all patients undergoing MICS with RPF (Zimmer Biomet, Jacksonville, FL, USA) at our institution. We analyzed in-hospital complications, as well as sternal complications and sternal pain at discharge and at follow-up 7 to 14 months after surgery. Results: Between June and December 2023, 12 patients underwent RPF during MICS, of which 9 patients were included in the study. The median (IQR) age was 64 years (63 to 71) and two patients (22%) were female. All patients underwent aortic valve replacement, with two patients (22%) undergoing concomitant aortic surgery. RPF was successfully performed in all patients. ICU and in-hospital stay were 1 day (1 to 1) and 9 days (7 to 13), respectively. Patients were first mobilized in the standing position on postoperative day 2 (2 to 2). Four patients (44%) required opiates on the general ward. In-hospital mortality was 0%. At discharge, rates of sternal pain, sternal instability or infection were 0%. After a follow-up time of 343.6 days (217 to 433), median pain intensity using the Visual Analog Scale was 0 (0 to 2). Forty-four percent (n = 4) of patients reported pain at rest. No sternal complications (sternal dehiscence, sternal mal-union, sternal instability, superficial wound infections and deep sternal wound infections) were reported. Conclusions: In the evolving landscape of cardiac therapies with incentives to reduce surgical burden, RPF showed safety and feasibility. It might become an important tool for sternal closure in minimally invasive cardiac surgery.